Texture evolutions of 5052 aluminum alloy sheets processed by dissimilar channel angular pressing - Han, JH; Oh, KH; Jee, KK; Chung, YH; Shin, MC (TRANS TECH PUBLICATIONS LTD, 2002)
Studies on texture evolutions were conducted on the 5052 Al alloy sheets using the developed dissimilar channel angular pressing (DCAP) to investigate the feasibility of this process for producing metallic sheets with the high formability and the low planar anisotropy. This process is capable of introducing the shear deformation into the metallic sheets in a continuous mode. ODFs were calculated for evaluating texture evolutions due to DCAP. The Lankford parameter ((r)-value) was determined using the measured pole figures to judge the formability and the planar anisotropy of the samples. The deep drawing tests were conducted to verify the validity of the calculated Delta(r-)value on evaluating the planar anisotropy. The production of the 5052 Al alloy sheets with a formability and a very low planar anisotropy could be possible by DCAP.
Keywords: SUBMICROMETER GRAIN-SIZE; STRIP